Peranan Sumber Daya Manusia dalam Mewujudkan Pertanian Indonesia yang Unggul - Tuti Supatminingsih (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2022)
It is known that in realizing superior agriculture it is necessary to have human resources that encourage agricultural excellence in Indonesia, Indonesia is famous for its natural wealth, one of which is from the agricultural system, human resources play an important role in this. However, in realizing superior Indonesian agriculture, there are also many obstacles or risks experienced by human resources in their role. In addition, the problem that is often faced is the limitation of counseling in the field which results in agricultural risks. (Buntuang, P. C. D., & Adda, H. W, 2018). The purpose of this study is to find out how people think about the role of resources in Indonesian agriculture, whether it's what efforts are being made to develop Indonesian agriculture to excel, what strategies are being carried out and what are the obstacles experienced in the process of developing superior Indonesian agriculture.